Pulse steroids serve in rhabdomyolysis secondary to strenuous exercise in a 17-year-old male - Naidu, G. Diwakar; Bayaram, Shravya; Goshika, Vaishnavi (International Journal Of Community Medicine And Public Health, 2024)
Rhabdomyolysis is a potentially life-threatening condition characterized by the breakdown of skeletal muscle fibers and the subsequent release of intracellular components, such as myoglobin and creatine kinase (CK), into the bloodstream. This case report describes a 17-year-old male who developed rhabdomyolysis secondary to strenuous exercise, specifically after performing 200 sit-ups. The patient presented with typical symptoms, including muscle pain, swelling, dark urine, and decreased urine output. Initial laboratory investigations revealed significantly elevated CK levels (193,500 U/L), indicating severe muscle damage. Prompt management included aggressive hydration, electrolyte monitoring, and supportive care. Notably, corticosteroid therapy (methylprednisolone) was initiated on day 3 based on consensus opinion and literature review, although the use of corticosteroids in rhabdomyolysis remains controversial. The patient’s condition improved with treatment, as evidenced by a gradual decline in CK levels and normalization of liver enzymes. Renal function remained stable, and the patient did not develop acute kidney injury, a potentially severe complication of rhabdomyolysis. This case highlights the importance of prompt recognition and aggressive management of exertional-induced rhabdomyolysis, particularly in young individuals engaging in strenuous physical activity. Early intervention, including corticosteroid therapy in selected cases, can help prevent potentially life-threatening complications and facilitate a successful outcome.